Patterned Deposition of Metal‐Organic Frameworks onto Plastic, Paper, and Textile Substrates by Inkjet Printing of a Precursor Solution1. (28th June 2013) - Zhuang, Jin‐Liang; Ar, Deniz; Yu, Xiu‐Jun; Liu, Jin‐Xuan; Terfort, Andreas
<x xml:space="preserve">Abstract</x> Flexible in many aspects: inkjet printing of metal‐organic frameworks permits their larger area, high‐resolution deposition in any desired pattern, even in the form of gradients or shades. When flexible substrates are used, many applications can be envisioned, such as sensing and capture of hazardous gases for personal safety measures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>